OsSWEET14 cooperates with OsSWEET11 to contribute to grain filling in rice. (May 2021) - Fei, Honghong; Yang, Zhipan; Lu, Qingtao; Wen, Xiaogang; Zhang, Yi; Zhang, Aihong; Lu, Congming
Highlights: OsSWEET14 is involved for grain filling in rice. OsSWEET14 exhibited distinct expression patterns during caryopsis development. OsSWEET14 cooperates with OsSWEET11 during grain filling in rice. Abstract: The grain-filling process is crucial for cereal crop yields, but how the caryopsis of such plants is supplied with sugars, which are produced by photosynthesis in leaves and then transported long distance, is largely unknown. In rice ( Oryza sativa ), various SWEET family sucrose transporters are thought to have important roles in grain filling. Here, we report that OsSWEET14 plays a crucial part in this process in rice. ossweet14 knockout mutants did not show any detectable phenotypic differences from the wild type, whereas ossweet14;ossweet11 double-knockout mutants had much more severe phenotypes than ossweet11 single-knockout mutants, including strongly reduced grain weight and yield, reduced grain-filling rate, and increased starch accumulation in the pericarp. Both OsSWEET14 and OsSWEET11 exhibited distinct spatiotemporal expression patterns between the early stage of caryopsis development and the rapid grain-filling stage. During the rapid grain-filling stage, OsSWEET14 and OsSWEET11 localized to four key sites: vascular parenchyma cells, the nucellar projection, the nucellar epidermis, and cross cells. These results demonstrate that OsSWEET14 plays an important role in grain filling, and they suggest that four major apoplasmic pathways supply sucrose to the endosperm during the rapid grain-filling stage via the sucrose effluxers SWEET14 and SWEET11.